EDUKASI PEMANFAATAN BAHAN ALAM UNTUK KEBERSIHAN GIGI PADA WARGA KELURAHAN KALIGAWE - Praptiningsih, Rahmawati Sri; Feranisa, Anggun (Faculty of Dentistry Universitas Islam Sultan Agung, 2024)
Background: Dental cavities or caries are ranked first in oral diseases in the world population. In Indonesia, RISKESDAS 2018 data shows that the greatest prevalence of caries is in the age groups of 5 years (93.4%), 12 years (68.8%), 15 years (68.1%), 35-44 years (92.1%) and 65-74 years (95.2%). Dental plaque control can use natural resources that are widely available in Indonesia. However, the proper use of natural materials and adequate knowledge of the advantages and disadvantages of each type of natural resource are very important for the success of dental plaque control in the community.Objective : This community service is to provide education about natural ingredients for dental health as well as the advantages and disadvantages of each ingredient to the Kaligawe Village community and provide education about oral health and the importance of maintaining dental hygiene to maintain oral homeostasis.Method: The methods used to increase community knowledge and awareness are counseling and interactive discussions.Result: The results of this community service include an increase in understanding and community interest.Conclusion: This educational activity has succeeded in increasing the knowledge and awareness of the Kaligawe Village community about the importance of dental hygiene and the use of natural substances.